Forecasting the Inequality of Income Distribution in Consequence of the Covid-19 Pandemic - Suparmono Suparmono; Anna Partina (Department of Development Economics, Universitas Sriwijaya, 2021)
This study aims to forecasting the Covid-19 Pandemic's effect on income inequality distribution in Kulon-Progo Regency during of 2020 to 2028. The study analysis tools utilized forecast are linear and non-linear trend. The historical data use during of 2010 to 2019, data source obtained from Central Bureau of Statistics Yogyakarta in statistical series book of 2020. The findings of forecast result show that the Covid-19 pandemic directly impact on the increased income inequality distribution. The implication is to carry out the process of economic recovery due to the Covid-19 pandemic case by identifying community groups who are vulnerable to decreased income through strengthening social safety nets. In addition, government policies can also optimize the utilization and transportation services to increase farmer exchange rates, because most people work in the agricultural sector.